THE INFLUENCE OF MOTIVATION, WORK DISCIPLINE AND SUPERVISION ON TEACHER PERFORMANCE AT KALIANGET 1 PUBLIC MIDDLE SCHOOL WITH SATISFACTION AS THE INTERVENING VARIABLE - Dewi, Nuning Nurna; Pradita, Fajar (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine the effect of motivation, work discipline and supervision on teacher performance at Kalianget 1 Public Middle School with satisfaction as the intervening variable. The population is 67 with saturated sampling technique. Data collection through questionnaires and data analysis using multiple linear regression and path analysis. The results of this study are: (1) There is an indirect effect of motivation on teacher performance through satisfaction. This is indicated by the t-value of the effect of motivation on satisfaction of 2.772 (2.772 > 1.96) and the t-count of the effect of satisfaction on performance of 6.583 (6.583 > 1.96); (2) There is an indirect effect of teacher discipline on teacher performance through satisfaction. This is indicated by the t-value of the influence of teacher discipline on satisfaction of 4.902 (4.902 > 1.96) and the t-count of the effect of satisfaction on performance of 6.583 (6.583 > 1.96); (3) There is an indirect effect of supervision on teacher performance through satisfaction. This is indicated by the t-value of the effect of motivation on satisfaction of 11.314 (11.314 > 1.96) and the t-count of the effect of satisfaction on performance of 6.583 (6.583 > 1.96).